Muhammad bin qasim ek azeem sipay salar - Dr. Abdul Rauf (Ferozesons; Pakistan, 2012)
Muhammad Bin Qasim: Ek Azeem Sipahi Salar highlights the life and military genius of Muhammad bin Qasim, the young commander who led the conquest of Sindh and left a lasting impact on history.